THE EFFECT OF INTEREST IN BEING A TEACHER, SELF-EFFICIENCY, AND FIELD EXPERIENCE PRACTICES ON PREPAREDNESS TO BE TEACHER: Study of Undergraduate Education Students at FE. Jakarta State University - Dian Mega Septianti; Sri Zulaihati; Achmad Fauzi (Yayasan Education and Social Center, 2022)
This study aims to examine the effect of interest in becoming a teacher, self-efficacy, and practice of field experience on readiness to become a teacher in undergraduate education study program students at the Faculty of Economics, State University of Jakarta. The research method used is descriptive quantitative method using primary data. The data collection technique uses a questionnaire/ questionnaire. The approach in this research is a simple random sampling approach. The number of samples is 167 people from 315 people (population). The results of the requirements analysis test showed that the data were normally distributed and had a linear relationship. Based on the partial test (ttest) it can be concluded that interest in becoming a teacher has a positive and significant effect on readiness to become a teacher, self-efficacy has a positive and significant effect on readiness to become a teacher, and the practice of field experience has no effect on readiness to become a teacher. While the joint regression coefficient test (Ftest) shows that interest in being a teacher, self-efficacy, and field experience practice affect the readiness to become a teacher and the coefficient of determination test (R2) shows that R square has a value of 0.532. It can be concluded that the magnitude of the influence of the variables of interest in becoming a teacher, self-efficacy, and practice of field experience on readiness to become a teacher is 53.2%. The conclusions that can be drawn in this study are interest in becoming a teacher, self-efficacy, and field experience practice as indicators of readiness to become a teacher, indicators of interest in becoming a teacher, self-efficacy, and field experience practice can be used by students for student readiness when becoming a teacher.